EFFECT OF PHOSPHORUS, POTASH AND RHIZOBIUM ON POD YIELD, NUTRIENT UPTAKE AND RESIDUAL AVAILABLE SOIL NPK OF VEGETABLE COWPEA - SWAROOP, KISHAN (Annals of Agricultural Research, 2014)
Field experiments were conducted during 2001 and 2002 at research farm of CARI, Port Blair using Arka Garima variety of vegetable cowpea to study the pood yield, nutrient uptake and residual available soil NPK by various levels of phosphorus potash and Rhizobium inoculation with andwithout nitrogen. The results revealed that maximum average yield of green pods was obtained with the application of 80 kg, P, 120 kg K, 20 kg N/na + Rhizobium inoculation. The length of root, uptake of phosphorus, available phosphorus, and potash in soil was recorded maximum with the application of 120 kg P, 120 kg K and 20 kg N + Rhizobium inoculation.